Manajemen Pengembangan Kultur Literasi di MTs Negeri Kota Batu - Fitriah, Nurlaeli (J-MPI (Jurnal Manajemen Pendidikan Islam), 2018)
Literacy is identified with reading and writing activities. With the passage of time literacy activities not only read and write. Literacy is defined as the ability to support, challenge, create, communicate and count using printed material and writing related to various contexts. Literacy that supports learning is literacy that allows individuals to achieve what they want to know, develop their knowledge and talents and support their participation in the community. This study aims to describe the management of the development of literacy culture, the implementation of the development of a culture of literacy and the evaluation of literacy culture development programs in MTs Negeri Kota Batu. This research uses qualitative with descriptive research types. The data sources used are primary and secondary. Data analysis used the Miles and Huberman analysis models. The results show the management carried out by the MTs Negeri Kota Batu under the coordination of the kepala madrasah and supported by the deputy of kepala madrasah in the fields of curriculum, infrastructure, public relations and financing. Not only that, for the success of the school management program, it also involves the madrasah committee. The implementation of the program in the form of habituating the dhuha prayer and reading Al-Qur’an, the habit of silent reading before learning, holding reading corners, programming the language of the month, and scientific writing training for teacher in collaboration with universities in Malang. Program evaluation carried out by the madrasah management is still anticipatory action. Its consideration is that the program is just implemented.